Analysis Of Marketing Strategies At Sakti Rajabasa Teknik In Bandar Lampung - Sakti Jaka Triasmara Syarif; Selfia Alke Mega (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this analysis is to find out the right marketing strategy to increase sales of Sakti Rajabasa Teknik. This analysis uses qualitative, an analytical tool that is used to discuss problems and find solutions in analyzing competitive strategies, namely by using SWOT Analysis (Strength, Weakness, Opportunity, Threats). This method is a method based on the strengths, weaknesses, opportunities and threats that come from the company or from outside the company or competitors. Based on the results of the research, the strategy that can be used by Sakti Rajabasa Teknik to increase sales is the Growth Strategy. Growth Strategy (Growth Strategy) Designed to achieve growth, both in sales, assets, profits, or a combination of the three. By minimizing costs (minimize costs) so as to increase profits. This method is the most important strategy at this time in the Sakti raabasa technical condition experiencing difficulties in controlling the rate of sales. How to minimize costs on Sakti Rajabasa Teknik as follows, look for distributors who are much cheaper than now but with the same quality so that this can be alleviated by minimizing the minimum costs, can increase revenue and Sakti Rajabasa Teknik can carry out price wars in an effort to increase market share. Thus, Sakti Rajabasa Teknik which has not yet reached critical mass (earned profit from large-scale production) will suffer defeat, unless this company can focus on certain profitable markets.